(untitled) (Journal of Plant Disease Sciences, 2020)
Field experiments were conducted at Rice Research Station, Moncompu, Alappuzha, Kerala for four consecutive seasons of Kharif 2017, Rabi 2017-18, Rabi 2018-19 and Kharif 2019 with the objective of evaluation of efficiency of newer and commercially available fungicides against rice sheath blight and glume discoloration diseases.The tested fungicides wereFlusilazole 12.5% + Carbendazim 25% SC, Azoxystrobin 18.2% W/W + Difenoconazole 11.4% W/W, Azoxystrobin 11%+Tebuconazole 18.3%W/W, Tricyclazole 18%+Mancozeb 62%WP, Zineb 68%+ Hexaconazole 4%WP, Mancozeb 50% + Carbendazim 25%WS, Fluxapyroxad 625g/L+Epoxiconazole 62.5G/L EC and Trifloxystrobin 25%+Tebuconazole 50% WG.Amongeight fungicides tested, Tricyclazole 18 % + Mancozeb 62% WP@2.5ml /lwas found most promisingcombination molecule against sheath blight and glume discoloration incidence followed by Zineb 68% + Hexaconazole 4% WP@ 2.5 g /l, Flusilazole 12.5 % + Carbendazim 25% SC @1ml /land Azoxystrobin 18.2% + Difenoconazole 11.4%w/w SC@1.0ml/l. The maximum yield was obtained from Flusilazole 12.5 % + Carbendazim 25% SC(5874 kg/ha) and Tricyclazole 18 % + Mancozeb 62% WP (5795 kg/ha) followed by Mancozeb 50 %+ Carbendazim 25%WS (5675 kg/a) and Zineb 68% + Hexaconazole 4% WP (5668 kg/ha). The control plot recorded with lowest yield of 3688 kg/ha.